Cleaning and sanitation in the food industry [video recording] Video Education Australasia. - Video Education Australasia (New York, N.Y. Films Media Group, 2009)
By ensuring customer safety, a food business also protects itself-from bad publicity, sinking profits, and even legal action. This program guides viewers through sanitation tools and procedures that are essential to the management of any food-related enterprise, including both food service outlets and food manufacturing facilities. Incorporating interviews with a cafe chef, a quality manager at a condiment factory, and the manager of a cleaning fluid distribution company, the film shows the proper steps for sanitizing dishes, utensils, floors, counters, culinary appliances, and assembly areas. Waste disposal and the storage of loose food items are also covered.
VCD
Keywords: Food -- Safety measures; Food supply; Food security; Food industry and trade; Food handling